Adaptive Evolution of Industrial Lactococcus lactis Under Cell Envelope Stress Provides Phenotypic Diversity - López-González, María Jesús; Escobedo, Susana; Rodríguez, Ana; Neves, A. Rute; Janzen, Thomas; Martínez, Beatriz (Frontiers in Microbiology, 2018)
Lactococcus lactis is widely used as a starter in the manufacture of cheese and fermented milk. Its main role is the production of lactic acid, but also contributes to the sensory attributes of cheese. Unfortunately, the diversity of suitable strains to be commercialized as dairy starters is limited. In this work, we have applied adaptive evolution under cell envelope stress (AE-CES) as means to provide evolved L. lactis strains with distinct physiological and metabolic traits. A total of seven strains, three of industrial origin and four wild nisin Z-producing L. lactis, were exposed to subinhibitory concentrations of Lcn972, a bacteriocin that triggers the cell envelope stress response in L. lactis. Stable Lcn972 resistant (Lcn972R) mutants were obtained from all of them and two mutants per strain were further characterized. Minimal inhibitory Lcn972 concentrations increased from 4- to 32-fold compared to their parental strains and the Lcn972R mutants retained similar growth parameters in broth. All the mutants acidified milk to a pH below 5.3 with the exception of one that lost the lactose plasmid during adaptation and was unable to grow in milk, and two others with slower acidification rates in milk. While in general phage susceptibility was unaltered, six mutants derived from three nisin Z producers became more sensitive to phage attack. Loss of a plasmid-encoded anti-phage mechanism appeared to be the reason for phage susceptibility. Otherwise, nisin production in milk was not compromised. Different inter- and intra-strain-dependent phenotypes were observed encompassing changes in cell surface hydrophobicity and in their autolytic profile with Lcn972R mutants being, generally, less autolytic. Resistance to other antimicrobials revealed cross-protection mainly to cell wall-active antimicrobials such as lysozyme, bacitracin and vancomycin. Finally, distinct and shared non-synonymous mutations were detected in the draft genome of the Lcn972R mutants. Depending on the parental strain, mutations were found in genes involved in stress response, detoxification modules, cell envelope biogenesis and/or nucleotide metabolism. As a whole, the results emphasize the different strategies by which each strain becomes resistant to Lcn972 and supports the feasibility of AE-CES as a novel platform to introduce diversity within industrial L. lactis dairy starters.